Assessment of Forest Road Network Alternatives for Pine Resin Extraction - Ahmad Budiaman; Heryana (Institut Pertanian Bogor (IPB University), 2013)
Pine resin, one type of non-timber forest products (NTFPs), is important for Indonesia. In addition to its high economic value, pine resin also has bright domestic and international market prospects. Utilization of commercial pine resin has been carried out in Indonesia, but the forest road network required for extracting pine resin has not been specifically planned. To date, the planning and selection of forest road network in forest management in Indonesia are intended only for the extraction of timber products and have not been integrated with the use of NTFPs; also, they have not considered the economic, ecological, and social aspects a whole. Planning and selection of forest road network have focused more on economic aspects only. This study aimed at planning and assessing the forest road network for extracting pine resin by considering the economic, ecological, and social criteria. Decision-making method used to select the best forest road network was utility analysis. Indicator used included road length, road density, a correction factor for manual carrying of pine resin, pine resin carrying distance, road construction cost, and productivity of carrying and extracting pine resin. The result of the utility analysis indicates that an alternative of forest road network for extracting pine resin has no the whole best indicators, but it has the highest utility value. This study suggested that the use of the utility analysis help the decision makers to selects process for forest road network alternative easily and rapidly.